Case report: Dramatic response to pralsetinib in an elderly patient with advanced RET-fusion positive papillary thyroid carcinoma - Nannini, Margherita; Repaci, Andrea; Ricco, Gianluca; Ianni, Manuela; Golemi, Arber; Maiolo, Vincenzo; Ferrari, Marco; Natali, Filippo; Rizzini, Elisa Lodi; Monari, Fabio; Solaroli, Erica; De Leo, Antonio; et al. (Frontiers in Oncology, 2022)
We are recently faced with a progressive evolution of the therapeutic paradigm for radioiodine refractory differentiated thyroid cancer (RAI-R DTC), since the advent of tissue agnostic inhibitors. Thus, tumor genotype assessment is always more relevant and is playing a crucial role into clinical practice. We report the case of an elderly patient with advanced papillary thyroid carcinoma (PTC) harboring RET-CCDC6 fusion with four co-occurring mutations involving PI3KCA, TP53, and hTERT mutations, treated with pralsetinib under a compassionate use program. Despite the high histological grade and the coexistence of aggressive RET co-mutations, an impressive metabolic and structural tumor response has been obtained, together with a patient's prolonged clinical benefit. A timely comprehensive molecular testing of those cases wild-type for the common thyroid carcinoma BRAF V600E-like and RAS-like driver mutations may uncover actionable gene rearrangements that can be targeted by highly selective inhibitors with great potential benefit for the patients.